RETRACTED: Di Paola et al. Combined Toxicity of Xenobiotics Bisphenol A and Heavy Metals on Zebrafish Embryos (Danio rerio). Toxics 2021, 9, 344 - Davide Di Paola; Fabiano Capparucci; Giovanni Lanteri; Marika Cordaro; Rosalia Crupi; Rosalba Siracusa; Ramona D’Amico; Roberta Fusco; Daniela Impellizzeri; Salvatore Cuzzocrea; Nunziacarla Spanò; Enrico Gugliandolo; et al. (Toxics)
The journal retracts the article entitled “Combined Toxicity of Xenobiotics Bisphenol A and Heavy Metals on Zebrafish Embryos (Danio rerio)” [...]